Politics of free trade in the Western Hemisphere - Pastor, Manuel (North-South Centre at the Univ. of Miami Coral GablesUS, 1996)
Analyzes the international and domestic factors that have contributed to commercial liberalization in Latin America, delineates the challenges that are beginning to surface, and takes a first step toward defining the research and policy agenda ahead.